2017
DOI: 10.3390/s17112548
|View full text |Cite
|
Sign up to set email alerts
|

Synergy Effect of Combining Fluorescence and Mid Infrared Fiber Spectroscopy for Kidney Tumor Diagnostics

Abstract: Matching pairs of tumor and non-tumor kidney tissue samples of four patients were investigated ex vivo using a combination of two methods, attenuated total reflection mid infrared spectroscopy and fluorescence spectroscopy, through respectively prepared and adjusted fiber probes. In order to increase the data information content, the measurements on tissue samples in both methods were performed in the same 31 preselected positions. Multivariate data analysis revealed a synergic effect of combining the two meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…During the in vivo studies, it was not impossible to certainly determine whether the exophytic and intracranial growth of tumor had occurred or not. Analysis of literature showed that usually registered fluorescence intensity under ultraviolet excitation has higher values in the intact area rather than in tumor [16][17][18][19][20] . Thus, it is possible to put forward a hypothesis that the first type spectra demonstrate the growth of tumor into the walls of the common bile duct.…”
Section: Resultsmentioning
confidence: 99%
“…During the in vivo studies, it was not impossible to certainly determine whether the exophytic and intracranial growth of tumor had occurred or not. Analysis of literature showed that usually registered fluorescence intensity under ultraviolet excitation has higher values in the intact area rather than in tumor [16][17][18][19][20] . Thus, it is possible to put forward a hypothesis that the first type spectra demonstrate the growth of tumor into the walls of the common bile duct.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the medical application of MIR is fewer than for NIR. MIR optical fibers have been commercially available since 2016, whereas previously laboratory tools existed only [12][13][14]. In a study, breast cancer imaging of 15 patients was carried out using mid-and long wave infrared cameras.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, it was demonstrated that a combination of fibre-optic approaches with the fusion of spectroscopic data from several methods increases the accuracy of sample differentiation by tens of percent [ 31 , 32 ]. Recently, authors demonstrated that a combination of a fibre-optic approach with the fusion of the spectroscopy data from several methods also increases the accuracy of tumour detection by 28% [ 33 ]. However, the majority of reported multispectral analyses present a combination of fluorescence and NIR spectroscopy methods [ 32 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latter enables the detection of different cancer types based on the qualitative and quantitative correlation of specific cancer biomarkers. MIR radiation penetrates the sample by up to 2 μm, which allows analysing individual cellular structures [ 33 ], while NIR radiation penetrates up to several mm into the tissue, allowing the evaluation of several tissue layers (e.g., epithelial cells, mucosa, muscular) [ 14 ]. We assume that this ability could vastly enhance the information collection process and become an essential part of the clinical translation of a new cancer diagnostic tool.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation